Systemic gene delivery to the central nervous system using Adeno-associated virus - Bourdenx, Mathieu; Dutheil, Nathalie; Bezard, Erwan; Dehay, Benjamin (Frontiers in Molecular Neuroscience, 2014)
Adeno-associated virus (AAV)-mediated gene delivery has emerged as an effective and safe tool for both preclinical and clinical studies of neurological disorders. The recent discovery that several serotypes are able to cross the blood-brain-barrier when administered systemically has been a real breakthrough in the field of neurodegenerative diseases. Widespread transgene expression after systemic injection could spark interest as a therapeutic approach. Such strategy will avoid invasive brain surgery and allow non-focal gene therapy promising for CNS diseases affecting large portion of the brain. Here, we will review the recent results achieved through different systemic routes of injection generated in the last decade using systemic AAV-mediated delivery and propose a brief assessment of their values. In particular, we emphasize how the methods used for virus engineering could improve brain transduction after peripheral delivery.